Photoconductivity in macroporous silicon with regular structure of macropores - Ivanov, V.I.; Karachevtseva, L.A.; Karas, N.I.; Lytvynenko, O.A.; Parshin, K.A.; Sachenko, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The effects of the increase of photoconductivity in periodic macroporous silicon structures depending on the size and period of cylindrical macropores are investigated. It is obtained that the ratio of macroporous silicon photoconductivity to bulk silicon photoconductivity achieves a maximum at the distance between macropores equal to two thicknesses of the Schottky layer, which corresponds to the experimental data. The increase of photoconductivity is due to both the large total surface area of macropores and the existence of Schottky layers in the near-surface region of cylindrical macropores.